PENGARUH GREEN ACCOUNTING DAN DIVIDEND PAYOUT RATIO TERHADAP FIRM SIZE MELALUI CSR SEBAGAI VARIABEL INTERVENING - Dewi, Mega Arisia (BISMA: Jurnal Bisnis dan Manajemen, 2020)
The purpose of this study was to analyze the effect of green accounting on firm size and corporate social responsibility, the effect of dividend payout ratio on firm size and corporate social responsibility, and the role of corporate social responsibility in mediating the effect of green accounting and dividend payout ratio on firm size. The sample used in this study was the branch offices of Bank Muamalat in East Java that selected using a purposive sampling technique. The data analysis method used was path analysis. The results of this study showed that green accounting has a significant positive effect on firm size. However, it had a negative significant effect on corporate social responsibility. The dividend payout ratio had a significant positive effect on firm size and corporate social responsibility. Corporate social responsibility mediated the effect of green accounting and dividend payout ratio on firm size. These results indicated that as more companies performing green accounting (environmental performance) will encourage more positive responses from investors and the community due to the increase of the dividends (as the impact of increased sales). These conditions will also increase the company size due to the increased positive image as the result of implementing environmental performance. Keywords: corporate social responsibility, dividend payout ratio, firm size, green accounting